Blockchain Meets Cloud: A New Era in Distributed Systems Architecture - Muskaan Mongia (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Blockchain and cloud technologies together constitute a major breakthrough in distributed systems architecture since they provide companies with unheard-of security, scalability, and operational efficiency. The symbiotic relationship between blockchain’s immutable ledger system and cloud computing’s scalable infrastructure is investigated in this article together with how their convergence opens fresh opportunities for business applications in supply chain management, financial services, and healthcare sectors. By means of the analysis of important architectural patterns, including Blockchain-as-a-Service (BaaS) and hybrid storage solutions, it shows how this integration addresses conventional constraints while enabling creative features such as automated compliance, real-time settlement systems, and improved data management. The article also looks at technical issues in security, interoperability, and scalability and suggests ways to use the capabilities of both technologies. Emerging technologies like artificial intelligence and IoT combined with evolving industry standards point to a transforming effect on how companies handle and use data in the digital economy as this paradigm develops.